The Effect of Dividend Policy on Share Price: A Conceptual Review - Raza, Hamad; Ramakrishnan, Suresh; Gillani, Syed Muhammad Ahmad Hassan; Ahmad, Humara (International Journal of Engineering and Technology, 2018)
In modern corporate world, dividend policy is one of the most debatable issues in corporate finance. The academic literature related to effect of dividend policy on share price has grown rapidly over the previous decade, due to its puzzling phenomena. The present study intends to conduct a non-systematic review of literature on the empirical and theoretical studies on corporate dividend policy in order to understand its nature and dimensions. In this concern, an extensive review of existing literature has been performed and it is found that there are three different approaches or schools of thought. First school of thought is that a rise in dividend payout will increase the firm value (share price). Second, thinks that a rise in dividend payout will reduce the firm value (share price) and third supports Miller and Modigliani (1) argument that firm value or share price are not affected by dividend policy. Till to date no consensus has appeared and results are inconclusive. This article also attempts to cover key empirical studies on dividend policy across countries, which shows that the phenomena of dividend policy differ from one country to another. The continuing nature and wide array of discussion on dividend policy has formulated a massive volume of literature that increase day by day. Therefore, it not feasible to do a full-fledge review of all debates.